Konsep arsitektur biomimetik pada bangunan Oseanarium - Adhelia Adjani Rahmah; Wafirul Aqli (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The concept of biomimetic in the Oceanarium building The concept of biomimetic architecture, which is rarely heard, has many advantages that can be applied to architectural work. The purpose of using the concept of biomimetic architecture is to maximize functions, achieve energy efficiency, and improve the quality of objects and user activities by applying one or more biological criteria from 11 biological criteria. The oceanarium building is a museum building with marine life as an object of the exhibition with functions as educational facilities, recreation facilities, observation centers, and marine life conservation facilities. The oceanarium building is one of the educational facilities that are most readily accepted by the public. This has become very important at this time where the need for education about biota and marine life is increasingly threatened by landfill and the uncontrolled fishing on a large scale. Research on architectural concepts in oceanarium buildings uses qualitative research methods. By collecting data and studies both from observation and literature. The conclusion in the form of the influence of the existence of each biological criterion applied to an oceanarium building.